Perbandingan Daya Output Panel Surya Rooftop Berdasarkan Gerak Semu Matahari Studi Kasus Kota Banda Aceh - Syukriyadin; Sara, Ira Devi; Syahrizal; Kadafi, Muamar (Journal of Engineering and Science, 2022)
The research aims to get the best slope of the solar module to be placed on the roof of the building. This research will look at the performance of solar panels with varying slopes from various types in the city of Banda Aceh. The method used in this research is data collection by looking at the most significant output power from various slopes and comparing it with calculating the output power. The data from each month will also be compared so that the cross panel and the best tilt angle will be. From the research that has been done, it is found that in December and January, with the sun's declination angle of 23 ° and 20 ° North Latitude, the orientation of the solar panel installation is facing south with the best tilt angle of the solar panel is 20 ° -25 ° in December and 18 ° -24 ° in January. In July, the sun's declination is 21.2 ° North Latitude. The orientation of the solar panel installation is facing North, with the best tilt angle of the solar panel being 15 °.